2020
DOI: 10.3390/agronomy10050628
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Rice Leaf Breaking Force by Temperature and Moisture Content to Reduce Breakage

Abstract: Leaf fragments and grain mixture produced by rice threshing with a combine harvester seriously affects the subsequent grain cleaning efficiency. In this paper, rice leaf breaking force was tested at different temperatures and moisture contents to analyze the influence of temperature on the tensile properties of rice leaves. The overlapping regions of rice leaf breaking force and grain separation force at different temperatures were obtained. Based on the rice leaf breaking force, the effect of the temperature … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 21 publications
(18 reference statements)
0
5
0
Order By: Relevance
“…The BM provides a higher tensile strength of 7.71 ± 1.21 MPa. One fascinating fact that came out from the mechanical property investigation was the high tensile strength of the BM compared to MIL, which is in total disagreement with the one proposed by Tang et al, 43 which says that succulent or fresh leaves tend to have a higher tensile strength than biofabricated materials. The MIL has a tensile strength of 5.4 ± 1.23 MPa, which shows lesser tensile strength than BM.…”
Section: Resultsmentioning
confidence: 82%
“…The BM provides a higher tensile strength of 7.71 ± 1.21 MPa. One fascinating fact that came out from the mechanical property investigation was the high tensile strength of the BM compared to MIL, which is in total disagreement with the one proposed by Tang et al, 43 which says that succulent or fresh leaves tend to have a higher tensile strength than biofabricated materials. The MIL has a tensile strength of 5.4 ± 1.23 MPa, which shows lesser tensile strength than BM.…”
Section: Resultsmentioning
confidence: 82%
“…For example, when rice leaves were dried by microwave, the cell wall is broken, which would change the tensile breaking property. Tang et al [40] carried out the tensile test of rice leaves under different temperatures and moisture. The results showed that moisture content had a greater impact on rice leaf breaking property.…”
Section: Table 3 Peak Tensile Breaking Force Of Rice Leaves In Differ...mentioning
confidence: 99%
“…The stalks of wheat are divided into above-ground part and underground part.The stalks of the underground part have secondary roots at the tiller nodes, and the stalks of the above-ground part are covered with leaf sheaths. The stalks of the above-ground part are generally 4-6 nodes, and the structure is similar to that of barley, rice and reed[18] . Support and transportation are two main functions of stalks.…”
mentioning
confidence: 94%